A banner year : studying religion and the enlightenment in 2019 (Editorial Introduction) - Cahill, Samara (2020)
Studies in Religion and Enlightenment (SRE) returns after a brief hiatus during the very busy spring and summer of 2019! This year was a milestone for eighteenth-century studies with the 50th Anniversary of the American Society for Eighteenth-Century Studies (ASECS) preceding the quadrennial congress of the International Society for Eighteenth-Century Studies (ISECS) in Edinburgh, Scotland. We at SRE believed 2019 would be an opportune year to take a snapshot of the robustness and diversity of religious content on the eighteenth-century studies conference circuit. This report chronologically surveys the major eighteenth-century conferences in 2019 and concludes with in-depth accounts of individual conferences by Tonya Moutray (reporting on H-WRBI) and Brijraj Singh (reporting on ISECS).